Determinants of integration and its impact on the economic success of immigrants: a case study of the Turkish community in Berlin - Alexander M. Danzer; Hulya Ulku (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Using a new data on 590 Turkish households in Berlin, we investigate the determinants and impact of integration on economic performance. We find that usual suspects such as time spent in Germany and education have positive impact, while networks have no impact on integration. There is strong evidence that political integration and the degree of full integration promote income. Using endogenous switching regression models, we show that local familial networks increase the income of unintegrated migrant groups only, while transnational networks decrease it. We also find that education is more welfare improving for integrated than non-integrated immigrants.
Keywords: O15; J15; C25; D10; 330; Integration; economic success; ethnic networks; Turkish migrants; Soziale Integration; Türken; Einkommen; Familie; Soziales Netzwerk; Ethnische Gruppe; Bildungsniveau; Berlin